Dysfunctional family as a factor in the acceptance of violence in intimate relationships - Farhodova , Umidabonu (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The paper examines the influence of a dysfunctional family on the formation of an individual’s perceptions of the self, interpersonal relationships, and the acceptability of violence in intimate relationships. Based on the analysis of psychological studies, it is shown that growing up in conditions of family dysfunction contributes to the normalization of violence, the development of dependent forms of behavior, emotional disturbances, and the reproduction of destructive patterns of interaction in adulthood.